Imposing Green Management to Enhance the Organizational Awareness against the Environmental Sustainability - Ramli, Yanto; Kurniawan, Deden; Imaningsih, Erna Sofriana; Yuliantini, Tine; Anah, Sri; Ali, Anees Janee (International Journal of Energy Economics and Policy, 2023)
Palm oil mill effluents (POME) not only abuse environment and causing harm to river and streams but also putting near by communities in danger due to severe health issues such as toxic infections, digestion disorder and skin diseases. Thereby, the present study intends to explore the organizational awareness and how it could be helpful to address the POME and POMS issues by turning it in to green resources that may provide solution to combat the issue and safe communities which are being affected by COP production. The sample of the study is the province of Indonesia; North Sumatera and purposive sampling method was used to sample the population. PLS methodology is used to analyze the data. Findings reveal that green management positively impacts organizational awareness, environmental concern and green technology. Moreover, organizational awareness, environmental concern and green technology plays crucial role in environmental sustainability.